1989
DOI: 10.1159/000199821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pectin, a Soluble Dietary Fiber, on Functional and Morphological Parameters of the Small Intestine in Rats

Abstract: We investigated the effects of pectin, a soluble dietary fiber, on functional and morphological parameters of the small intestine in rats. A control group and a pectin-fed group were given a fiber-free elemental liquid diet and an elemental liquid diet containing 2.5% (w/w) pectin, respectively, for 2 weeks. The ileal mucosal specific activities of maltase, sucrase and alkaline phosphatase increased significantly in the pectin-fed group. Maltose absorption of the ileum, studied in vitro by the method of everte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…These findings are consistent with the studies of Chun et al (1989) and Lizardo et al (1997) who reported an increase in brush border enzyme activity with increasing levels of soluble fiber in rats and pigs, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with the studies of Chun et al (1989) and Lizardo et al (1997) who reported an increase in brush border enzyme activity with increasing levels of soluble fiber in rats and pigs, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous studies showing significantly reduced small intestinal AP activity after addition of soluble dietary fibers (pectin and guar gum) to the rat diet (4,12). In contrast, another rat study using dietary pectin reported elevated ileal specific AP activity (6). At the present time, the available data on the impact of pectin on somatic, feeding and intestinal parameters are in some cases controversial.…”
Section: Discussionsupporting
confidence: 89%
“…The impact of pectin supplementation on intestinal enzyme activity is inconsistent. Some animal studies have revealed that in pectin-fed rats the specific AP activity was significantly reduced in the upper jejunum in comparison with rats fed with basal diets (4); other results indicate that pectin stimulates ileal mucosal specific activities of AP, maltase and sucrase (6). At the present time, however, information concerning the relation between pectin feeding, intestinal enzyme activity and obesity development is lacking.…”
Section: Introductionmentioning
confidence: 90%
“…Dietary fibres possess unique chemical and physical characteristics responsible for eliciting an array of physiological responses. Soluble dietary fibres have favourable effects on gastrointestinal functions, since they can delay gastric emptying (Sanaka et al 2007), slow transit time through the small intestine (Lorenzani, 1998) and stimulate proliferation of intestinal cells (Chun et al 1989;Fukunaga et al 2003).…”
mentioning
confidence: 99%